The roles of CD38 and CD157 in the solid tumor microenvironment and cancer immunotherapy - Wo, Yu Jun (2020)
The tumor microenvironment (TME) consists of extracellular matrix proteins, immune cells, vascular cells, lymphatics and fibroblasts. Under normal physiological conditions, tissue homeostasis protects against tumor development. However, under pathological conditions, interplay between the tumor and its microenvironment can promote tumor initiation, growth and metastasis. Immune cells within the TME have an important role in the formation, growth and metastasis of tumors, and in the responsiveness of these tumors to immunotherapy. Recent breakthroughs in the field of cancer immunotherapy have further highlighted the potential of targeting TME elements, including these immune cells, to improve the efficacy of cancer prognostics and immunotherapy. CD38 and CD157 are glycoproteins that contribute to the tumorigenic properties of the TME. For example, in the hypoxic TME, the enzymatic functions of CD38 result in an immunosuppressive environment. This leads to increased immune resistance in tumor cells and allows faster growth and proliferation rates. CD157 may also aid the production of an immunosuppressive TME, and confers increased malignancy to tumor cells through the promotion of tumor invasion and metastasis. An improved understanding of CD38 and CD157 in the TME, and how these glycoproteins affect cancer progression, will be useful to develop both cancer prognosis and treatment methods. This review aims to discuss the roles of CD38 and CD157 in the TME and cancer immunotherapy of a range of solid tumor types.